The Development of the Logical Conception of the Right of Izmirli Ismail Haqqi - Hande Nur Bozbuğa (İslam Tetkikleri Dergisi)
Izmirli Ismail Haqqi (1869-1946) was a thinker who lived in the last years of the Ottoman Empire and the first years of the Turkish Republic. Numerous studies have investigated his life and scientific personality. He wrote about various fields of Islamic thought. An essential aspect of his versatile personality is his understanding of logic. His works Mi‘yâru’l-ulûm, Ilm-i mantık, Mantık-ı tatbîkî veya fenn-i esâlib, Mantık-ı tatbîkî yahut fenn-i üslûb, Felsefe Dersleri and Fenn-i menâhic are related to the field of logic. The main argument of our study was that there is a development in Izmirli’sconception of logic from classical to modern, or in Izmirli’s words, from old to new. He argued that Aristotelian logic could be combined with new logic studies of science in the west in the modern period. Another issue discussed in this study is the lithographed copyright of his three volumes of logic, method, and metaphysics in library records, which has not been referenced so far. Our claim here is that one of these studies, whose publication place and date are unknown, Ilm-i mantık, was later copyrighted as Felsefe Dersleri, whereas Mantık-ı tatbîkî was later copyrighted as Fenn-i menahic by Izmirli. The comparison of the content of the works reveals that the systematic and content almost completely overlap, thus supporting our claim.